2021
DOI: 10.3390/encyclopedia1030060
|View full text |Cite
|
Sign up to set email alerts
|

Age-Friendly Built Environment

Abstract: Age-friendly built environments have been promoted by the World Health Organisation (WHO, Geneva, Switzerland) under the Global Age-friendly Cities (AFC) movement in which three domains are related to the built environment. These are: housing, transportation, outdoor spaces and public buildings. The aim is to foster active ageing by optimising opportunities for older adults to maximise their independent living ability and participate in their communities to enhance their quality of life and wellbeing. An age-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…It shows that the aged who live alone have higher demands on their community environment than those who live with their partners or children. The finding supports the study by Chau and Jamei [ 25 ], who reported that the aged who live alone or lost a partner are more likely to suffer from loneliness, and therefore require more social support. It is also consistent with previous studies examined in this research that loneliness leads to great dependence on the community environment [ 80 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It shows that the aged who live alone have higher demands on their community environment than those who live with their partners or children. The finding supports the study by Chau and Jamei [ 25 ], who reported that the aged who live alone or lost a partner are more likely to suffer from loneliness, and therefore require more social support. It is also consistent with previous studies examined in this research that loneliness leads to great dependence on the community environment [ 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…Yu et al [ 15 ] argued that improving the physical environment can help reduce pedestrian hazards on the road, enhance perimeter accessibility, and encourage outdoor activities. Some countries have issued design guidelines, such as the Lifetime Homes Design Guide in the UK and Australia’s Livable Housing Design Guidelines, to provide a comfortable living environment for the aged [ 25 ]. Sweden has also attempted to eliminate physical environmental barriers with housing renovations [ 26 ].…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Although age-friendly built environment aspects are addressed in [ 18 ], the technology aspects are not included in that study.…”
Section: Progress Beyond the State Of The Artmentioning
confidence: 99%
“…This greater difficulty in moving around in the community, imposed by the characteristics of the environment, can lead to the need for assistance, as our work suggests, with obstacles on ramps, sidewalks, parks, and squares. If older people can feel comfortable and safe in public spaces, their willingness to spend time outdoors will increase [ 39 ]. Outdoor green spaces, in particular, can play an important role in promoting active aging through physical activities, social relationships, and community participation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%